2019
DOI: 10.21873/invivo.11559
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofMDM2, TP53andP14ARFPolymorphisms on Endometrial Cancer Risk and Onset

Abstract: Background/Aim: The aim of this study was to determine the joint effect of single nucleotide polymorphisms (SNPs) of MDM2, TP53, and CDKN2A (P14ARF) genes on the onset and course of endometrial cancer (EC) in postmenopausal women. Materials and Methods: The study group consisted of 144 EC women and 50 non-cancer controls. MDM2 rs22279744, TP53 rs1042522, and P14ARF rs3088440, rs3731217, and rs3731245 SNPs were analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Studies on correlations between p14ARF and endometrial cancer have, so far, been rather not numerous, while p14ARF is a component of the p53 pathway (p14ARF/MDM2/p53), essential for the development and progression of various in vivo 34: 943-951 (2020) human neoplasms, including EC (4,5,22). Certain modulations in EC cells kinetics, possible via alterations in this pathway, [p14ARF/p53/p21(WAF1)], may result from a correlation between Sox9 and NF-ĸB signalling mechanisms, as well as from the Akt status (26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies on correlations between p14ARF and endometrial cancer have, so far, been rather not numerous, while p14ARF is a component of the p53 pathway (p14ARF/MDM2/p53), essential for the development and progression of various in vivo 34: 943-951 (2020) human neoplasms, including EC (4,5,22). Certain modulations in EC cells kinetics, possible via alterations in this pathway, [p14ARF/p53/p21(WAF1)], may result from a correlation between Sox9 and NF-ĸB signalling mechanisms, as well as from the Akt status (26).…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account our previous studies, we demonstrated that the SNP309 polymorphism of the MDM2 gene is strongly associated with EC (both the GG genotype and the G allele), while the TP53 codon 72 polymorphism has been of a prognostic value and useful for the prophylaxis from EC (the Arg/Arg homozygote has been linked with an increased, while the Pro/Arg heterozygote and the Pro allele -with a decreased EC risk) (35)(36)(37). Moreover, the research about the joint effect of MDM2 SNP309, TP53 rs1042522, and the three currently described P14ARF polymorphisms on the onset of EC in postmenopausal women, concluded that MDM2 SNP309 plays a role in this cancer (22). The multiple-SNP combinations G-Arg-C-T-G for MDM2, TP53, and the three P14ARF polymorphisms, increased EC risk, while the T-Arg-C-T-G variants decreased risk for disease (22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Overexpression or amplification of this gene has been detected in a variety of malignant carcinomas. 16,17 Studies have also determined that MDM2 309 T > G SNP were also correlated with an increased risk of solid tumors. Luan et al reported that MDM2 T309 G polymorphism may contribute to NSCLC susceptibility, especially in the Asian population and women.…”
Section: Discussionmentioning
confidence: 99%